The treatment of bone metastases with single fraction or multiple fractions with 3D CRT or SBRT: systematic review article - Ferrão, Ana Rita Camarate (2022)
Introduction – The choice of treatment depends on several factors, including the clinical status and prognosis of each patient. These factors play an important role in the choice of therapeutic intervention in bone metastases. Early detection and the right treatment can improve the quality of life and functional independence of patients. Methodology – This article aims to systematically review the literature of the past 15 years, identifying the different types of fractionation (single fraction versus multiple fractions) and techniques used in radiotherapy in the treatment of bone metastases. Results – Recent advances in technology and radiotherapy treatment techniques assist in the distribution of highly conformational doses and imaging guidance for more precise delivery of treatment. Stereotactic body radiotherapy (SBRT) allows us to define and increases the dose in the tumor to irradiate. In the case of bone metastasis, results from the control of local tumors and pain have proved promising. Conventional radiotherapy 8Gyx1, however, remains the preferred treatment in palliative patients. Conclusion – The treatment of bone metastasis is complex, and a multidisciplinary approach is always necessary. Treatment should be individualized to fit the symptoms and clinical status of each patient.